Effects of Emergency Medical Service Response Time on Survival Rate of Out-of-Hospital Cardiac Arrest Patients: a 5-Year Retrospective Study - Siriporn Damdin; Satariya Trakulsrichai; Chaiyaporn Yuksen; Pungkava Sricharoen; Karn Suttapanit; Welawat Tienpratarn; Wijittra Liengswangwong; Suteenun Seesuklom (Archives of Academic Emergency Medicine)
Introduction: Emergency medical service (EMS) response time is a critical factor in managements of out-of-hospital cardiac arrest (OHCA) cases. This study aimed to investigate the effects of EMS response time on survival of OHCA patients.